ANALYSIS OF EDUCATION-BASED CHILD MARRIAGE PREVENTION THROUGH THE GENERATION PLANNING PROGRAM (GENRE) - Yusroni, Ahmad; Haryono, Bambang Santoso; Nuh, Mohammad (Erudio Journal of Educational Innovation, 2024)
The social phenomenon of child marriage is something that often occurs in various regions in Indonesia. This is due to the lack of public understanding of the importance of the maturity of the age of marriage and also not understanding the negative impact of child marriage. In increasing public understanding, the government launched the Generasi Berencana (Genre) Program with the aim of preparing family life for teenagers, especially education, work and marriage with full planning. This article aims to analyze Education-based Child Marriage Prevention through the GenRe Program of DPPKB Malang Regency based on the theory of policy implementation effectiveness according to Riant Nugroho (2020). The research method used is literature study and secondary data analysis. The results showed that the prevention of child marriage through the GenRe program in Malang district was said to be effective, where three of the five indicators were appropriate, namely the right policy, right implementer, and right target indicators, while the right environment and right process indicators were not optimal.